Diurnal Differences in Intracellular Replication Within Splenic Macrophages Correlates With the Outcome of Pneumococcal Infection - Hames, Ryan G.; Jasiunaite, Zydrune; Ercoli, Giuseppe; Wanford, Joseph J.; Carreno, David; Straatman, Kornelis; Martinez-Pomares, Luisa; Yesilkaya, Hasan; Glenn, Sarah; Moxon, E. Richard; Andrew, Peter W.; Kyriacou, Charalambos P.; et al. (Frontiers in Immunology, 2022)
Circadian rhythms affect the progression and severity of bacterial infections including those caused by Streptococcus pneumoniae, but the mechanisms responsible for this phenomenon remain largely elusive. Following advances in our understanding of the role of replication of S. pneumoniae within splenic macrophages, we sought to investigate whether events within the spleen correlate with differential outcomes of invasive pneumococcal infection. Utilising murine invasive pneumococcal disease (IPD) models, here we report that infection during the murine active phase (zeitgeber time 15; 15h after start of light cycle, 3h after start of dark cycle) resulted in significantly faster onset of septicaemia compared to rest phase (zeitgeber time 3; 3h after start of light cycle) infection. This correlated with significantly higher pneumococcal burden within the spleen of active phase-infected mice at early time points compared to rest phase-infected mice. Whole-section confocal microscopy analysis of these spleens revealed that the number of pneumococci is significantly higher exclusively within marginal zone metallophilic macrophages (MMMs) known to allow intracellular pneumococcal replication as a prerequisite step to the onset of septicaemia. Pneumococcal clusters within MMMs were more abundant and increased in size over time in active phase-infected mice compared to those in rest phase-infected mice which decreased in size and were present in a lower percentage of MMMs. This phenomenon preceded significantly higher levels of bacteraemia alongside serum IL-6 and TNF-α concentrations in active phase-infected mice following re-seeding of pneumococci into the blood. These data greatly advance our fundamental knowledge of pneumococcal infection by linking susceptibility to invasive pneumococcal infection to variation in the propensity of MMMs to allow persistence and replication of phagocytosed bacteria. These findings also outline a somewhat rare scenario whereby the active phase of an organism’s circadian cycle plays a seemingly counterproductive role in the control of invasive infection.